Daya Saing Komoditas Padi Sawah di Kecamatan Biboki Moenleu Kabupaten Timor Tengah Utara Provinsi Nusa Tenggara Timur - Umbu Joka; Yohanes Pebrian Vianney Mambur (Fakultas Pertanian, Universitas Timor, 2020)
This study aims to analyze competitiveness (comparative advantage and competitive advantage) as well as to analyze the impact of government policies on input prices (fertilizer subsidies) and output (basic price of grain) on lowland rice farming income in Biboki Moenleu District, North Central Timor Regency. This research was conducted from July to August 2020. The sample was determined using simple random sampling technique, namely randomly totaling 100 farmers. The types of data used are primary data and secondary data. The data analysis method used is descriptive qualitative method and Policy Analysis Matrix (PAM). Results of the study: 1) Rice farming in Biboki Moenleu District, North Central Timor Regency has a competitive advantage with a Private Cost Ratio (PCR) value of 0.19 and a comparative advantage in a Domestic Resource Cost Ratio (DRCR) of 0.13 so that lowland rice farming is feasible to continue. . 2). The government policy on input-output prices for lowland rice farming in Biboki Moenleu District, North Central Timor Regency has a significant impact on the income of lowland rice farmers at private prices with a Nominal Protection Coefficient on Tradable Output (NPCO) value of 1.13 and a Subsidy Ratio of Producer (SRP) of 0.05.